2007
DOI: 10.4049/jimmunol.179.11.7593
|View full text |Cite
|
Sign up to set email alerts
|

Role of STAT3 in CD4+CD25+FOXP3+ Regulatory Lymphocyte Generation: Implications in Graft-versus-Host Disease and Antitumor Immunity

Abstract: Immunological tolerance is maintained by specialized subsets of T cells including CD4+CD25+FOXP3+ regulatory cells (Treg). Previous studies established that Treg thymic differentiation or peripheral conversion depend on CD28 and Lck signaling. Moreover, foxp3 gene transfer in murine CD4+CD25− T lymphocytes results in the acquisition of suppressive functions. However, molecular pathways leading to FOXP3 expression remain to be described. In this study, we investigated the molecular events driving FOXP3 expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
97
2
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(109 citation statements)
references
References 61 publications
7
97
2
1
Order By: Relevance
“…This observation was consistent with the previous report that TGF-b1 production was induced by the stimulation with anti-CD3 and anti-CD28 Abs in human CD4 + CD25 2 T cells (42). Moreover, costimulation of CD28 induces STAT3 phosphorylation in CD4 + CD25 2 T cells (43). We think STAT3 plays an important role, because enhanced phosphorylation of STAT3 in Egr-3-transduced cells was demonstrated under CD28 costimulation (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…This observation was consistent with the previous report that TGF-b1 production was induced by the stimulation with anti-CD3 and anti-CD28 Abs in human CD4 + CD25 2 T cells (42). Moreover, costimulation of CD28 induces STAT3 phosphorylation in CD4 + CD25 2 T cells (43). We think STAT3 plays an important role, because enhanced phosphorylation of STAT3 in Egr-3-transduced cells was demonstrated under CD28 costimulation (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…impaired the downstream phosphorylation of STAT3 in CD4 C T cells; 20 to answer this question, a pharmacologic model was used to measure NKG2D expression on mouse and human CD8 C T cells after CD28 stimulation in the presence or absence of the Lck inhibitor PP2, the JAK/STAT inhibitor AG490, or the STAT3 inhibitor JSI-124. As expected, activation of CD28 by CD80 binding elevated STAT3 phosphorylation as early as 15 min and NKG2D expression in CD8 C T cells.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study demonstrated that CD28 triggers JAK/STAT3 signaling via Lck in CD4 C T cells. 20 We thus established a pharmacologic model to determine whether Lck/ZAP70, as an upstream kinase cascade, activates STAT3 in CD8 C T cells. Mouse and human CD8 C T cells were enriched (Fig.…”
Section: Cd28 Activation In Cd8 C T Cells Triggers Increased Nkg2d Exmentioning
confidence: 99%
See 1 more Smart Citation
“…Suppressing Treg has been shown to be effective in enhancing the immune response of host cells to cancer cells [31,32]. Importantly, studies have shown that constitutively activated Stat3 is involved in these events [33]. Taken together, this evidence suggests that constitutively activated Stat3 not only functions as an initiator for oncogenesis but is also involved in interactions between cancer cells and their microenvironment.…”
Section: Introductionmentioning
confidence: 99%